Effect of volumetric energy density on microstructure and tribological properties of FeCoNiCuAl high-entropy alloy produced by laser powder bed fusion. (8th December 2020) - Ren, Yaojia; Liang, Luxin; Shan, Quan; Cai, Anhui; Du, Jingguang; Huang, Qianli; Liu, Shifeng; Yang, Xin; Tian, Yingtao; Wu, Hong
ABSTRACT: A near-equiatomic FeCoNiCuAl High-entropy alloy (HEA) was produced using laser powder bed fusion (L-PBF) pre-alloy powder. Microstructural characteristics and tribological properties of L-PBF specimens under various volumetric energy densities ( VED s) were investigated in detail. The results showed that the phase of L-PBF specimen consisted of BCC matrix + Cu-rich B2 precipitate. The microstructure of L-PBF specimen largely consisted of columnar grains perpendicular to the melt pool boundary (MPB) direction owing to the epitaxial growth along the temperature gradient. The preferred orientation of the L-PBF specimen was gradually transformed from the order of <001> to <101> as the VED rose. Larger size precipitates re-appeared and wider MPB were formed upon faster remelting and steeper cooling as a result of higher VED . Compared to the components produced by spark plasma sintering (SPS), L-PBF specimens presented better wear resistance owing to the ultra-fine substructure and nano-scaled precipitates. In addition, the L-PBF specimen produced with 83 J/mm 3 VED exhibits the highest elastic strain to failure ( H / Er ) and yield stress ( H 2 / E r 3 ).